Genetic polymorphism in high hbf anemic pregnant women and the effect of stem cell factor and erythropoietin-treated K562 cells on erk signaling of mapk pathway - Za'ror, Yousef Saeed Mohammad Abu (2023)
Anemia is one of the most common conditions in pregnant women due to acquired or genetic dysregulation. Dysregulation of hemoglobin (Hb) including fetal hemoglobin (HbF) due to single-nucleotide polymorphism (SNP) have been reported to cause anemia in pregnancy. Several genetic loci, including DNA polymorphisms at B-cell lymphoma 11A (BCL11A), HMIP-2, and XmnI, have a significant influence on HbF levels. K562 human chronic myelogenous leukemia cells, on the other hand, have an embryonic HbF phenotype and are widely used as a screening model for HbF inducers. K562 cell differentiation is associated with an increase in the expression of embryo-fetal globin genes such as γ-globin genes. Krüppel-like factor 1 (KLF1), BCL11A, and MYB regulate the γ-globin gene. Hence, this study intended to determine the association of HbF level and DNA polymorphism at BCL11A rs1186868, rs6545816, and rs1427407, HMIP-2 rs9376090, and XmnI rs7482144 in anemic pregnant women visiting Hospital Universiti Sains Malaysia. In this study, a total of 164 anemic pregnant women (Hb <11 g/dl) were recruited and 27% exhibited high level of HbF (> 1%). High-performance liquid chromatography was used to determine the HbF and HbA2 levels. Multiplex ARMSPCR and gap-PCR were used to detect mutations and deletion at the β-globin gene cluster in 44 samples with high HbF levels respectively. From 22 samples, 15 mutations were detected at the β-globin gene while no mutation at the δβ-globin gene. Samples without these mutations were genotyped for allelic discrimination for BCL11A rs1186868, HMIP‑2 rs9376090, and XmnI rs7482144 by using real-time PCR, while Sanger DNA sequencing was performed for the BCL11A gene at rs6545816 and rs1427407. Based on SNPs, allele G at SNP BCL11A rs1186868 could possibly contribute as HbF-promoting alleles. Furthermore, there was no significant difference in HbF levels between genotypes for the SNPs HMIP‑2 rs9376090, XmnI rs7482144, BCL11A rs6545816, and BCL11A rs1427407. On the other hand, growth factors such as stem cell factor (SCF) and erythropoietin (EPO) are important for erythropoiesis, and the second part of this study was aimed to elucidate the effect of these growth factors on the expression of γ-globin mRNA levels, BCL11A, KLF1, and the ERK of the mitogen‑activated protein kinase (MAPK) pathway, on the K562 cell line. K562 cells were treated for 24 hours with SCF, EPO, or a combination of both and expression of γ- globin mRNA, BCL11A and KLF-1 as well as the expression of the MAPK pathway (ERK and pERK) were determined. A combination of SCF and EPO treatment increased γ- globin expression. Furthermore, these growth factors were demonstrated to promote BCL11A and KLF1 protein expressions differently, although via the same signaling pathway which is the MAPK pathway. In conclusion, high HbF levels in anemic pregnant women was not associated by BCL11A, HMIP-2, and XmnI genetic polymorphisms and growth factors such as SCF and EPO has the potential to be included in management of hemoglobinopathies through its promoting effect via MAPKpathway.